Circular Economy and Cooperativism: a review of the literature on the contribution of inter-cooperation to transformation - Vázquez Boasso, Lili María Inés; Imaz, Oier (Cooperativismo & Desarrollo, 2025)
Faced with the major challenges posed by climate change, such as the disappearance of natural resources and excess waste, it is possible to analyse valuable experiences of cooperatives that strive to incorporate the principles of the circular economy into their management. In this way, cooperatives link caring for people, which is at the heart of their activity, with their concern for the environment. To understand these experiences and how business models are being developed to achieve this incorporation, a literature review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, focusing on business models and inter-cooperation strategies. The analysis of the selected literature is developed in relation to four main thematic areas: vision and concept of the circular economy; the role of companies; the case of cooperatives; and collaborative paths, i.e., industrial symbiosis, networks and clusters, and inter-cooperation. The results suggest that, although cooperatives are better placed than conventional companies to face the transformations required by a vision, concept and practices that transform the circular economy, overcoming barriers requires collaboration between cooperatives and, above all, other actors. To this end, a legal framework is needed to facilitate such collaboration, as well as detailed documentation of experiences in different contexts to enable dialogue and learning from each other about the use of tools that facilitate the path towards the transformation of their business models.